A review of Bukit Asah camping ground of Karangasem, Bali - Susanto, Budi; Dewi, Ni Wayan Miranda Aprita; Sinambela, Mario Togi Parlindungan; Saputra, I Komang Ari Wijaya; Savitry, Gusti Ayu Devi Succi Pramitya Maha; Setiawan, Indra (Journal of Commerce, Management, and Tourism Studies, 2023)
This research aims to explore the application of Sapta Pesona, the seven aspects of tourist attraction, in the context of Taman Harmoni Bali Campground, a popular tourist destination in Bali, Indonesia. The study investigates how Taman Harmoni Bali Campground incorporates these seven aspects to enhance the overall tourist experience and attract a diverse range of visitors. The methodology employed in this research includes a combination of qualitative and quantitative approaches. Data collection involves conducting interviews with the management of Taman Harmoni Bali Campground, as well as surveys administered to a sample of tourists who have visited the campground. The interviews aim to gain insights into the strategies and practices employed by the management to implement Sapta Pesona, while the surveys aim to assess the perceptions and satisfaction levels of tourists regarding their experience at the campground. The findings of this study provide a comprehensive analysis of the application of Sapta Pesona in Taman Harmoni Bali Campground. The research reveals that the campground effectively integrates all seven aspects of Sapta Pesona, including security, order, cleanliness, coolness, beauty, hospitality, and memories. The results of the study also demonstrate the positive impact of implementing Sapta Pesona in Taman Harmoni Bali Campground. The application of these seven aspects contributes to an enhanced tourist experience, leading to higher levels of visitor satisfaction, increased tourist arrivals, and positive word-of-mouth recommendations. This research contributes to the understanding of how Sapta Pesona can be effectively implemented in a tourist attraction, specifically in the context of Taman Harmoni Bali Campground. The findings provide valuable insights for the management of other tourist destinations seeking to enhance their attractiveness and improve the overall visitor experience. Additionally, the study highlights the significance of sustainable tourism development by incorporating local cultural elements and maintaining environmental integrity while promoting tourism in Bali.